Preliminary Study on the Biodegradability of Chitosan Films Emulsified with Palm Oils (Aracaceae) from the Brazilian Cerrado - Reis, Arlete Barbosa dos; Arrudas, Sônia Ribeiro (Journal of Research Updates in Polymer Science, 2020)
Non-toxic products with distinguishable characteristics are desirable for use in the packaging sector. Biopolymers fit this criterion and can serve as vehicles for the addition of various compounds, such as enzymes, dyes, antioxidant agents, or monounsaturated fatty acids, to provide useful qualities to a product, such as biodegradability. A biopolymer obtained from fishing industry waste residues can be combined with fatty acids to form films and emulsions with different characteristics to be used in different drug production, packaging, and product protection. This study aimed to use a natural biopolymer, chitosan, in combination with oils from the Mauritia flexuosa L.f., (“buriti”) and Acrocomia aculeata (“macaúba”) species of palm trees to develop films that exhibit excellent biodegradability in soil. The degradation of chitosan films (CF), emulsified chitosan films with buriti oil (CFB), and emulsified chitosan films with macaúba oil (CFM) in soil was investigated, where the CFB samples showed the best protection against moisture and the largest weight reduction over 30, 60, and 90 day testing periods. Further studies are needed to test the practical application of these films, but the results of the CFB sample indicate that these chitosan films imbued with natural oils from the Mauritia flexuosa L.f. and Acrocomia aculeata species have great potential for use in the packaging sector.